2007
DOI: 10.1016/j.bmcl.2007.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of desformylflustrabromine and its evaluation as an α4β2 and α7 nACh receptor modulator

Abstract: Desformylflustrabromine (dFBr; 1) and desformylflustrabromine-B (dFBr-B; 2) have been previously isolated from natural sources, and the former has been demonstrated to be a novel and selective positive allosteric modulator of alpha4beta2 nicotinic acetylcholine (nACh) receptors. The present study describes the synthesis of water-soluble salts of 1 and 2, and confirms and further investigates the actions of 1 and 2 using two-electrode voltage clamp recordings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 19 publications
6
80
0
Order By: Relevance
“…In contrast, consistent with previous results (Kim et al, 2007;Weltzin and Schulte, 2015), we found that dFBr potentiates both (a4) 3 (b2) 2 and (a4) 2 (b2) 3 nAChRs, increasing ACh maximal responses with little effect on ACh EC 50 . We also found that CMPI at 1 mM, a concentration that produces maximal potentiation, did not prevent further potentiation of (a4) 3 (b2) 2 nAChR by dFBr and vice versa (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, consistent with previous results (Kim et al, 2007;Weltzin and Schulte, 2015), we found that dFBr potentiates both (a4) 3 (b2) 2 and (a4) 2 (b2) 3 nAChRs, increasing ACh maximal responses with little effect on ACh EC 50 . We also found that CMPI at 1 mM, a concentration that produces maximal potentiation, did not prevent further potentiation of (a4) 3 (b2) 2 nAChR by dFBr and vice versa (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…1), isolated originally from the marine bryozoan Flustra foliacea (Peters et al, 2002), acts as a neuronal nAChR PAM, enhancing, at concentrations ,1 mM, peak ACh responses of a4b2 (Sala et al, 2005;Kim et al, 2007;German et al, 2011) and a2b2 (Pandya and Yakel, 2011) nAChRs expressed in Xenopus oocytes. At higher concentrations, dFBr inhibited these receptors and a7 nAChRs (Kim et al, 2007). Subcutaneous administration of dFBr to rats resulted in reduced nicotine self-administration (Liu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown no apparent potentiation of other subtypes, including ␣7 and ␣3␤4 (Sala et al, 2005;Kim et al, 2007). On ␣4␤2 receptors, coapplication of increasing concentrations of dFBr with a fixed concentration of ACh produces a bell-shaped dose-response curve containing both stimulatory (Ͻ10 M dFBr) and inhibitory components (Ͼ10 M dFBr) (Kim et al, 2007).…”
Section: Introductionmentioning
confidence: 84%
“…Previous studies using dFBr extracted from Flustra foliacea suggested potentiation may be a result of altered channel gating kinetics (Sala et al, 2005). At inhibitory concentrations of dFBr "rebound" or "hump currents" have been observed, suggesting dFBr inhibition may be attributable to open-channel block (Kim et al, 2007).…”
Section: Introductionmentioning
confidence: 97%